Anti-cancer properties of Caulerpa racemosa by altering expression of Bcl-2, BAX, cleaved caspase 3 and apoptosis in HeLa cancer cell culture - Permatasari, Happy Kurnia; Wewengkang, Defny Silvia; Tertiana, Nur Iedha; Muslim, Farida Zharfani; Yusuf, Muhammad; Baliulina, Shintya Octaviana; Daud, Vanessa Pradna Adyana; Setiawan, Aurielle Annalicia; Nurkolis, Fahrul (Frontiers in Oncology, 2022)
The main cause of cervical cancer is infection with Human Papilloma Virus (HPV). Loss of apoptotic control allows cancer cells to survive longer and allows time for mutation accumulation thereby increasing the ability to invade during tumor development. Treatment options for cervical cancer today are surgery, radiotherapy, and chemotherapy. Toxicity to normal cells, adverse side effects, and drug resistance are the main barriers to the use of chemotherapy. Among marine organisms such as bacteria, fungi, actinobacteria, and seaweed have been used for the treatment of cancer. Caulerpa has bioactive metabolites, namely alkaloids, terpenoids, flavonoids, steroids and tannins and its bioactivity has been reported against many diseases including cancer. This study aimed to evaluate the anticancer activity of C. racemosa on HeLa cervical cancer cells. The study used a true experimental post-test only control group design to determine the effect of C. racemosa extract on HeLa cancer cells. C. racemosa extract was given in doses of 50 μg/mL, 100 μg/mL, 200 μg/mL, and 0 μg/mL as controls. Quantitative measurement of apoptosis was measured using flowcytometry and the expression of Bcl-2, BAX, and cleaved-caspase 3 as pro and anti-apoptotic proteins was measured using immunofluorescence. Trypan blue exclusion test was performed to measure cell viability. C. racemosa extract significantly increased the expression of pro-apoptotic proteins BAX and cleaved caspase-3 compared to controls. Annexin V-PI analysis showed the induction of apoptosis in treated cells and decreased HeLa cell viability at 24 hours and 48 hours post-treatment (p-value <0.05). C. racemosa extract has potential as an anti-cancer with pro-apoptotic and anti-proliferative activity on HeLa cancer cells and can be explored further as a cervical cancer therapy.